Developing Students’ Note Taking Skills through Cornell Format - Yuniarti Yuniarti; Ika Kana Trisnawati (Proceedings of AICS - Social Sciences, 2018)
Note taking is a type of activity that is inseparable in the academic settings; for example, making short notes on a lecture, creating a list of to-do assignments, or re-writing ideas from a textbook. However, these note taking activities are often done without any particular system since the majority of Indonesian students have little knowledge on how to properly take notes. In this study, the aim was to develop students’ note taking ability by introducing them to a note taking format, commonly known as Cornell notes. The study employed two-cycle class action research to implement the Cornell format to a total of 15 students of English Education Department of University of Muhammadiyah Aceh. The students were asked to take notes by following the procedure in the Cornell format, in which it required the students to write in short phrases/sentences in four blank columns: heading, cue, note taking, and summary. The students’ note taking results were compared to a note taking criteria adapted from AVID, which used a four-scale category. Findings indicated that, in general, ten out of 15 students were in the “fair” category and four were in the “good” category, while only one was “poor”, in taking proper notes by using the Cornell format in cycle I. These results further improved in the cycle II wherein five students had been in the “excellent” category, seven reached the “good” category, and the remaining three were “fair”. The students were eventually able to do appropriate note taking by using the Cornell format, and this suggests that the students can make a good habit in note taking if they apply a correct method. Further, they can also make a summary out of a long written text so that they can easily review and learn a topic better.Keywords:Note taking, Cornell Format.